2006
DOI: 10.1063/1.2189123
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Non-Expanding Universe: Surface Brightness Data From HUDF

Abstract: Surface brightness data can distinguish between a Friedman-Robertson-Walker expanding universe and a non-expanding universe. For surface brightness measured in AB magnitudes per angular area, all FRW models, regardless of cosmological parameters, predict that surface brightness declines with redshift as (z+1)^-3, while any non-expanding model predicts that surface brightness is constant with distance and thus with z. High-z UV surface brightness data for galaxies from the Hubble Ultra Deep Field and low-z data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…This disagreement could, however, be solved by an increase of luminosity at higher redshift due to the evolution of galaxies. For SNIa [97] or GRBs [98], for which it is supposed there is no evolution, the standard model works, provided that an ad hoc dark energy constant is included and we assume zero evolution and negligible extinction or selection effects (which are not universally accepted; [99,100,101] [110] observed that Lubin & Sandage used a very involved evolutionary k-correction scheme, with many adjustable assumptions and parameters to correct observed high-z surface brightness. These evolutionary and K-corrections are subject to uncertainty and cannot be used convincingly.…”
Section: Time Dilation Testmentioning
confidence: 99%
“…This disagreement could, however, be solved by an increase of luminosity at higher redshift due to the evolution of galaxies. For SNIa [97] or GRBs [98], for which it is supposed there is no evolution, the standard model works, provided that an ad hoc dark energy constant is included and we assume zero evolution and negligible extinction or selection effects (which are not universally accepted; [99,100,101] [110] observed that Lubin & Sandage used a very involved evolutionary k-correction scheme, with many adjustable assumptions and parameters to correct observed high-z surface brightness. These evolutionary and K-corrections are subject to uncertainty and cannot be used convincingly.…”
Section: Time Dilation Testmentioning
confidence: 99%
“…Lerner [110] proposed a test of the evolution hypothesis that is also useful in the present case. There is a limit on the ultraviolet surface brightness (UV SB) of a galaxy because, when the surface density of hot bright stars and thus supernovae increases, large amounts of dust are produced to absorb all the UV except that from a thin layer.…”
Section: Cosmic Chronometersmentioning
confidence: 99%
“…However, their claim, rather than being a Tolman test, was that the evolution of galaxies can explain the difference between the results of the Tolman test and their preferred model, which includes expansion. Lerner [110] observed that Lubin & Sandage used a very involved evolutionary k-correction scheme, with many adjustable assumptions and parameters to correct observed high-z surface brightness. These evolutionary and K-corrections are subject to uncertainty and cannot be used convincingly.…”
Section: Cosmic Chronometersmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy derived from the annihilation of protons and electrons would produce a background radiation of X-and γ-rays. In more recent times, some proposers of plasma cosmology (e.g., Brynjolfsson, 2004;Lerner, 2006) have stated that there is no expansion, the Universe is static, and that the redshift of the galaxies would be explained by some kind of tired light effect of the interaction of photons with electrons in the plasma.…”
Section: Plasma Cosmologymentioning
confidence: 99%